Sluggish Cognitive Tempo (SCT), Comorbid Psychopathology, and Functional Impairment in College Students: The Clinical Utility of SCT Subfactors. Issue 3 (February 2023) - Nelson, Jason M.; Lovett, Benjamin J.
Background: Sluggish cognitive tempo (SCT) has been proposed to be either its own distinct disorder or a transdiagnostic process. Objective: To examine SCT within ADHD (and its specific presentations) and internalizing disorders and its relationship with functional impairment, particularly when considered from a multidimensional perspective. Method: Undergraduate students (N = 2, 806) completed self-report scales measuring SCT, ADHD, anxiety, depression, and functional impairment. The SCT scale consisted of three subfactors identified in prior research. Results: Students with internalizing disorders were equally as likely as those with ADHD to report clinically significant SCT, and having multiple other disorders predicted especially high levels of SCT symptoms. Only sleepy/sluggish symptoms incrementally predicted impairment. Conclusions: These findings provide more support for SCT as a transdiagnostic process than as a distinct disorder. All areas of SCT symptoms are associated with ADHD, anxiety, and depression, but the sleepy/sluggish symptoms may be uniquely associated with problems in everyday living.